2003
DOI: 10.1002/ajmg.a.10169
|View full text |Cite
|
Sign up to set email alerts
|

Mandibuloacral dysplasia with absent breast development

Abstract: hormone (TSH), and serum-free thyroxine (FT4) levels were in the normal range. IGF1, IGFBP3, LHRH, and estradiol levels were also normal, as was her glucose tolerance test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…They ranged in age from four to 37 years, were originally diagnosed as MAD (17 patients from 12 families) or HGPS (5 patients from 2 families); and together had four different homozygous or compound heterozygous LMNA mutations and two compound heterozygous ZMPSTE24 mutations. A 21‐year‐old woman with a homozygous A529V LMNA mutation lacked breast development, although she attained menarche at age 10 and had regular menstruation cycle [Cogulu et al, 2003; Garg et al, 2005]. The woman we described with a homozygous A529T LMNA mutation and menarche at age 13 also lacked breast development.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They ranged in age from four to 37 years, were originally diagnosed as MAD (17 patients from 12 families) or HGPS (5 patients from 2 families); and together had four different homozygous or compound heterozygous LMNA mutations and two compound heterozygous ZMPSTE24 mutations. A 21‐year‐old woman with a homozygous A529V LMNA mutation lacked breast development, although she attained menarche at age 10 and had regular menstruation cycle [Cogulu et al, 2003; Garg et al, 2005]. The woman we described with a homozygous A529T LMNA mutation and menarche at age 13 also lacked breast development.…”
Section: Discussionmentioning
confidence: 88%
“…To date, a total of 22 patients have been reported to have MAD and LMNA or ZMPSTE24 mutations (Table I) [Schrander‐Stumpel et al, 1992; Tudisco et al, 2000; Novelli et al, 2002; Agarwal et al, 2003; Cao and Hegele, 2003; Cogulu et al, 2003; Shen et al, 2003; Simha et al, 2003; Plasilova et al, 2004; Garg et al, 2005]. They ranged in age from four to 37 years, were originally diagnosed as MAD (17 patients from 12 families) or HGPS (5 patients from 2 families); and together had four different homozygous or compound heterozygous LMNA mutations and two compound heterozygous ZMPSTE24 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Breast development is reduced to absent [180]. An autosomal recessive variant of MAD with generalized loss of adipose tissue (MADB, MIM # 608612) is due to mutations in Zmpste 24, i.e.…”
Section: V1 Mandibuloacral Dysplasiamentioning
confidence: 99%
“…Simha et al (2003) and Shen et al (2003) reported the same R527H homozygous mutation in patients of different ethnicities). Homozygous Arg527His and Ala529Val mutations in the LMNA gene have been reported previously in MADA (Cogulu et al, 2003;Garg et al, 2005;Kosho et al, 2007). The last reported MADA case with the LMNA mutation was the R527C mutation in the LMNA gene (Luo et al, 2014).…”
Section: Resultsmentioning
confidence: 95%